Spatiotemporal Control of CRISPR/Cas9 Function in Cells and Zebrafish using Light‐Activated Guide RNA. Issue 23 (6th April 2020) - Zhou, Wenyuan; Brown, Wes; Bardhan, Anirban; Delaney, Michael; Ilk, Amber S.; Rauen, Randy R.; Kahn, Shoeb I.; Tsang, Michael; Deiters, Alexander
Abstract: We developed a new method for the conditional regulation of CRISPR/Cas9 activity in mammalian cells and zebrafish embryos using photochemically activated, caged guide RNAs (gRNAs). Caged gRNAs are generated by substituting four nucleobases evenly distributed throughout the 5′‐protospacer region with caged nucleobases during synthesis. Caging confers complete suppression of gRNA:dsDNA‐target hybridization and rapid restoration of CRISPR/Cas9 function upon optical activation. This tool offers simplicity and complete programmability in design, high spatiotemporal specificity in cells and zebrafish embryos, excellent off‐to‐on switching, and stability by preserving the ability to form Cas9:gRNA ribonucleoprotein complexes. Caged gRNAs are novel tools for the conditional control of gene editing, thereby enabling the investigation of spatiotemporally complex physiological events by obtaining a better understanding of dynamic gene regulation. Abstract : A light‐activated gRNA allows for precise spatiotemporal control of gene editing by CRISPR/Cas9 in both mammalian cells and zebrafish embryos, with excellent off‐to‐on switching. This highly programmable approach can be easily adapted to any desired target sequence and can be delivered to a variety of organisms in the form of ribonucleoprotein complexes.